Blütenlese, Getreideernte oder Baumfällung? Untersuchungen zum kanonorientierten und sprachsensiblen Philosophieunterricht mit Ganzschriften - Albus, Vanessa (Ganzschriften im Philosophie- und Ethikunterricht. Anachronismus in Zeiten der Digitalisierung oder Gegengewicht zur Häppchenkultur?)

Werner Stegmaier: Formen philosophischer Shriften. Zur Einführung. Hamburg: Junius 2021. 288 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Nachwuchs-Café (reloaded): Standortbestimmungen - Rumlich, Dominik; Matz, Frauke (Standortbestimmungen in der Fremdsprachenforschung)

The Offering of Incense: Jewish Mystical Perspectives on Disease and Healing* - Ackermann, Domenik (Dialog)
Abstract An examination of a passage from the Zohar on Exodus (2:218b‐219b) provides Jewish mystical perspectives on disease, which may help inform a Christian response of solace and healing to illness and suffering in general, and to the COVID‐19 pandemic in particular. The aforementioned passage in the Zohar describes the preparation of incense. The primary purpose of the portion maintains that incense has special healing powers that even relieve people from severe diseases. The relating Midrash Ha‐Ne'lam explains the passage further by referring to the 4th century Palestinian Rabbi Aha arriving at a town that struggles with an epidemic. It describes how R. Aha initiates a ritual containing a study of the Talmud on incense, after which the village is healed from the epidemic. The Jewish theological background and reception of the passage may shed new light on how ritual and sensory experience can alleviate the experience of disease and suffering.
Keywords: Religious studies

Esteem and Self-Esteem in the British and the French Moralists: A Comparative Approach. (Rivista di filosofia)

Esteem and Self-Esteem in Early Modern Ethics and Politics. (Intellectual History Review)

“Helvétius and his Critics: Esteem, Benevolence and the Question of the Diminution of the Individual.” - Blank, Andreas (Historia Philosophica)

“Helvétius and Bentham on the Morality of the Desire for Esteem.” - Blank, Andreas (Rivista di filosofia)

“Self-Deception and Illusions of Esteem: Contextualizing Du Châtelet’s Challenge.” - Blank, Andreas (Époque Émilienne. Philosophy, Science and Culture in the Age of Émilie Du Châtelet.)

“Confessionalization and Natural Philosophy.” - Blank, Andreas (The Cambridge History of Philosophy of the Scientific Revolution.)

“Santorio and Leibniz on Natural Immortality: The Question of Emergence and the Question of Emanative Causation.” - Blank, Andreas (Santorio Santori and the Emergence of Quantified Medicine.)

“Common Notions and Immortality in Digby and the Early Leibniz.” - Blank, Andreas (The Philo-sophy of Kenelm Digby (1603–1665).)

Rezension von Martin Mulsow und Asaph Ben-Tov (eds.), Knowledge and Profanation. Transgressing the Boundaries of Religion in Pre-Modern Scholarship - Blank, Andreas (Quellen und Forschungen aus italienischen Archiven und Bibliotheken)

“Jacob Schegk on Plants, Medicaments and the Question of Emergence.” - Blank, Andreas (Mechanism, Life and Mind in Modern Natural Philosophy.)

“Julius Caesaer Scaliger.” - Blank, Andreas (Encyclopedia of Renaissance Philosophy)

Fortunio Liceti - Blank, Andreas (Encyclopedia of Renaissance Philosophy)

“Pharmacology in the Renaissance.” - Blank, Andreas (Encyclopedia of Renaissance Philosophy)

„Die Räume richtig auseinanderhalten“. Anmerkungen zum Politischen im Gegenwartstheater. - Eke, Norbert (Wege der Germanistik in transkultureller Perspektive. Akten des XIV. Kongresses der Internationalen Vereinigung für Germanistik (IVG))

Du Châtelet's Libertarianism - Wells, Aaron (History of Philosophy Quarterly)
Abstract There is a growing consensus that Emilie Du Châtelet's challenging essay “On Freedom” defends compatibilism. I offer an alternative, libertarian reading of the essay I lay out the prima facie textual evidence for such a reading. I also explain how apparently compatibilist remarks in “On Freedom” can be read as aspects of a sophisticated type of libertarianism that rejects blind or arbitrary choice. To this end, I consider the historical context of Du Châtelet's essay, and especially the dialectic between various strands of eighteenth-century libertarianism and compatibilism.
Keywords: Philosophy

Science and the Principle of Sufficient Reason: Du Châtelet contra Wolff - Wells, Aaron (HOPOS: The Journal of the International Society for the History of Philosophy of Science)
Keywords: History and Philosophy of Science